Bank personnel administration : a basic plan - McCurry, Charles M.; Bank Administration Institute (Park Ridge, Ill. : Bank Administration Institute, 1975)
This manual was written to assist those who are responsible for personnel programs, particularly in community banks. It covers the essential principles and practices of good personnel administration- the basic foundation for the development and refinement of an organized purposeful personnel plan.
A report prepared for Bank Administration Institute's Personnel Administration Commission.
ne 10/04/2019
Loans
Keywords: Banks and banking